Narrow vessels cavitate first during a simulated drought in Eucalyptus camaldulensis - Barigah, Tete Severien (2021)
Establishing drying-limits for mortality of different tree species and understanding the anatomical and physiological traits involved is crucial to predict forests' responses to climate change. The xylem of Eucalyptus camaldulensis presents a complex of solitary vessels surrounded by different imperforate tracheary elements and parenchyma that influence, in a poorly known way, its hydraulic functioning. We aimed at describing the dynamics of embolism propagation in this type of xylem, seeking any vessel-size pattern, and unraveling the threshold of xylem embolism leading to nonrecovery after drought in E. camaldulensis. We assigned potted saplings to a protracted water-stress for 70 days. We relied on colorimetric and hydraulic methods to test for links between xylem anatomy and embolism propagation in the main stem. On average, the occurrence of embolism was randomly distributed in the stem xylem, but the probability of embolized vessels was higher than predicted by chance in the narrowest vessels of individuals that experienced low to moderate water-stress. The saplings could recover from severe water-stress if their percentage loss of conductance (PLC) was <77%, but not when the PLC was ˃ 85%. We concluded that, contrary to results reported for most species, the narrowest vessels are the most vulnerable to cavitation in E. camaldulensis, suggesting a lack of tradeoff between xylem efficiency and safety (in response to drought) at the tissue level. These results challenge the well-established paradigm of the effect of vessel size on cavitation, which states that the widest conduits are the most vulnerable to both freeze–thaw and drought-induced cavitation.